PENGGUNAAN METODE PECS (PICTURE EXCHANGE COMMUNICATION SYSTEM) UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI ANAK AUTIS DI SKH NEGERI 01 KOTA SERANG - Nurul Futuhat; Dr. Hj. Isti Rusdiyani, M.Pd; Toni Yudha Pratama, M.Pd (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2018)
Abstract  The purpose of this research is to find out and expose communication skills autistic children especially on his expressive communication skills, by way of responding to the orders given by the teacher in the form of differentiating the images through the use of PECS method. The application of this method of PECS just until phase III of phase VI method. The type of research that used Single Subject Research design with A1-B-A2. Data obtained in this study were analyzed with descriptive statistics. The components analyzed include the analysis and analysis between the conditions. The effectiveness of the methods of PECS shows that there is an increase of condition A1-B-A2. On phase distinguishing ability test score A1 image data acquired by the average percentage of 44.4%, next on phase B percentage of data obtained with average 76.94, and on the phase A2 retrieved data with the average percentage of 72.2%. The data is supported with 0% overlap percentage which indicates that this method can increase the the expressive communication abilities on one autistic child in Special Education Need 01 Serang City with a target behavior take pictures right from the many possibilities (differentiating the images).